When I Were a Meerkat - Davies, Andrew (London Portico, 2011)
Uses the best-selling format established for the 100,000 selling When I Were A Lad From the same author/photographer combination as When Cats Assassinate, The Thoughts of Chairman Miaow and Gnomes of the Silver Screen Capitalises on the BIG LOVE for meerkats first generated by the BBC series Meerkat Manor
Include Illustrations
Keywords: English wit and humor